Generation paths of online public opinion impact in public health emergency: a fuzzy-set qualitative comparative analysis based on Chinese data - Teng Liu; Xiangming Hu; Qiangqiang Dong (Frontiers Media S.A., 2024)
Public health emergencies can quickly provoke alarm and shock in the society, as well as generate high-impact online public opinion through network fermentation. Analyzing the generation mechanism of online public opinion in public health emergencies helps to explain its characteristics and laws. Based on information ecology theory, seven indicators from the four dimensions of information person, information, information technology, and information environment are extracted, and the analysis framework of public opinion impact of public health emergencies is constructed. Taking 40 cases from China as samples, fuzzy set qualitative comparative analysis (fsQCA) is used to investigate the generation path and mechanism of online public opinion impact in public health emergency. The results suggest that: information person and information technology are the core conditions for the generation of high-impact online public opinion, but the harm level contained in the information itself is not sensitive to the generation of public opinion impact; there are four generation paths and three types that drive the generation of high-impact online public opinion in public health emergencies. This work enriches the cognition of the causality of public opinion impact in public health emergencies from the perspective of configuration, and clearly shows which combination of variables leads to high-impact online public opinion, and helps to prevent and reduce the risk of public opinion.